XL2S Pan Borneo vs Rajang river boardgame 2.0 (empowering fitness and fun: a board game for Inclusive physical activity among people with disabilities) - Kram, Suhardi; Sullah, Abbylolita; Mohd Sanif, Siti Nurr Atika; Nikol, Luke; Che Abu Shafie, Asmalini; Jemat Anchang, Gordon Nicolaus; Jeck, Ashley Irenaeus (Universiti Teknologi MARA, Kedah, 2023)
Regular physical activity are important in keeping people physically and mentally healthy. However, lack of fun, poor access to facilities and unsafe environments are the reasons for most people to skip physical activity (Anderson, Carter & Smith, 2021). According to Johnson, Thompson, & Davis, (2022), fun is considered one of the main reasons people involved in physical activity. Thus, XL2S Pan Borneo VS Rajang River Boardgame 1.0 was created as a tools for sedentary people from different ages to start exercise in a fun and interesting way. However, 1.0 version was not suitable to be play by people with disabilities. Therefore, XL2S Pan Borneo Vs Rajang River Boardgame 2.0 will be introduced to empowerfitness and fun among disabled people. This innovative boardgame is designed to address the issue of limited motivation for physical activity among individuals with disabilities due to their medical conditions and challenges. By combining the joy of play with simple exercises in a group setting, the product aims to enhance the health and well-being of this demographic.Drawing inspiration from "snake and ladder" and "monopoly" games, the objective of the game is to be the first player to reach the end by moving across the board while perform a variety of exercises from square one to the final square. The exercise selection are following the ACSM’s exercise prescription guidelines comprises basic movements using elastic bands and free weight exercise guidance provided in the game set, ensuring accessibility andeffectiveness for disabled players. Symbolic elements from Sarawak landmark like Pan Borneo and Rajang River add to the experience, representing setbacks and progress, respectively. To access exercise instructions, players can scan QR codes on the manual making it convenient and inclusive for all. By gamifying exercise and social interaction, the game promotes inclusivity and allows players with disabilities to participate alongside friendsand support groups (Lee, Martinez, & Robinson, 2023). Regular game play encourages low- impact physical movements, improving strength, flexibility and also coordination. Research on well-being to measure the effectiveness of this product on people with disabilities is still under the proposal process. The boardgame combats sedentary lifestyles associated with prolonged bed rest, commonly faced by individuals with disabilities. With its focus on fun and camaraderie, it encourages players to actively pursue physical activity.